Nilai Moral Dalam Kumpulan Cerpen Ustad Salim Menangis Karya Budi Maryono - Rista Helmalia Putri; Siti Ulfiyani; Muhajir Muhajir (Lembaga Pengembangan Kinerja Dosen, 2023)
The purpose of this research is to describe and find out the moral values ​​contained in the collection of short stories by Ustad Salim Menangis by Budi Maryono. This study uses a qualitative method. The approach used in this study is a qualitative descriptive approach and sociology of literature. The data collection technique used in this study was listening, reading, and taking notes. The technique of presenting research data uses informal techniques. The data analysis technique used in this research is content analysis. The results of the study show that there is a moral value contained in the collection of short stories by Ustad Salim Crying by Budi Maryono. There are three types of moral values, namely the human relationship with oneself, the human relationship with God, and the human relationship with the social sphere and the natural environment. The moral values ​​of human relations with oneself include working hard, promising, having principles, responsibility, managing time, never giving up, awareness, regret, and self-improvement. The moral values ​​of human relations with God include praying, trusting God, worshiping God, second chances from God, sacrifice, and surrender. The moral values ​​of human relations with the social sphere and the natural environment include caring, helping, loving, respecting, family responsibilities, advice, helping each other, establishing hospitality, and mother's love.